Exploring the effects of concept mapping on undergraduate students’ EFL reading comprehension in China - Ta, Na; Razali, Abu Bakar; Razali, Fazilah (Sciedu Press, 2023)
Reading is a fundamental life-long learning tool to achieve personal and professional success, and it has been attached with great importance in China. However, despite the significance of reading comprehension, EFL undergraduate students in China face challenges when reading in English language. It is essential for both teachers and researchers to explore effective teaching techniques to teach reading. In this regard, concept mapping can serve as a specific form of teaching and learning technique for reading instruction. The present study employed a quasi-experiment to investigate the effects of concept mapping on the EFL reading comprehension of undergraduate students in China. The study spanned 32 instructional sessions, and the effects on knowledge retention were measured two weeks after the experiment. The participants included 135 second-year undergraduate students from three intact EFL classes at a university in China. The findings revealed that the use of concept mapping technique was effective in improving students‟ reading comprehension. Moreover, the combined use of concept mapping with conventional method was more effective than fully using concept mapping in promoting students‟ reading comprehension and knowledge retention. The study gives pedagogical and policy implications for teachers, syllabus designers, curriculum developers, and other stakeholders.